2022
DOI: 10.3390/pharmaceutics14102119
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Guidelines Regarding Dihydropyrimidine Dehydrogenase (DPD) Deficiency Screening Using Uracil-Based Phenotyping on the Reduction of Severe Side Effect of 5-Fluorouracil-Based Chemotherapy: A Propension Score Analysis

Abstract: Dihydropyrimidine dehydrogenase (DPD) deficiency is associated with severe fluoropyrimidines-induced toxicity. As of September 2018, French recommendations call for screening for DPD deficiency by plasma uracil quantification prior to all fluoropyrimidine-based chemotherapy. A dose reduction of fluoropyrimidine is recommended when uracil concentration is equal to or greater than 16 ng/mL. This matched retrospective study assessed the impact of DPD screening on the reduction of severe side effects and on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…This may also be a result of inter-laboratory variability, as observed in several previous studies. 29,37 To our knowledge, this study was also the first to describe several patients who underwent a second uracil concentration measurement. Intraindividual test reproducibility should be considered to evaluate its accuracy.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This may also be a result of inter-laboratory variability, as observed in several previous studies. 29,37 To our knowledge, this study was also the first to describe several patients who underwent a second uracil concentration measurement. Intraindividual test reproducibility should be considered to evaluate its accuracy.…”
Section: Discussionmentioning
confidence: 86%
“…This may also be a result of inter-laboratory variability, as observed in several previous studies. 29,37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In the genotyping group, we found that 6% of our patients carried nonfunctional DPYD variants, which is in line of prior findings (4% in the report by Pallet et al 11 and about 8% in three other studies 1,8,14 ). In the phenotyping group, 2% of patients were poor metabolizers, a lower percentage than previously reported (e.g., 16% in the study by Laures et al 15 and 7% in Pallet et al 11 ). However, this percentage should be interpreted with caution, given the small size of this group (n = 41).…”
Section: Discussionmentioning
confidence: 53%
“…The use of pre-therapeutic uracilemia and subsequent adaptive dosing should not be questioned as it allows a decrease in the rate of 5-FU toxicity. 26 However, DPD phenotyping using uracil concentrations might be misleading in patients with impaired renal function. If the patients are dialyzed, even if false-positive results could not be excluded, phenotyping of DPD deficiency should preferably be carried out with samples collected after dialysis.…”
Section: Discussionmentioning
confidence: 99%